Association of laboratory markers and cerebral blood flow among sickle cell anemia children - Adanho, Corynne Stéphanie Ahouéfa; Yahouédéhou, Sètondji Cocou Modeste Alexandre; Santana, Sânzio Silva; Vieira, Camilo; Santiago, Rayra Pereira; de Santana, Jeanne Machado; Pitanga, Thassila Nogueira; Aleluia, Milena Magalhães; Maffili, Vítor Valério; Leite, Ivana Paula Ribeiro; Zanette, Dalila Luciola; Lyra, Isa Menezes; et al. (Frontiers in Pediatrics, 2022)
Background: Stroke is one of the highest complications of sickle-cell anemia (SCA). The Transcranial Doppler (TCD) has been adopted worldwide as a gold standard method for detecting alterations in the blood velocity in cerebral arteries. In this study, we investigated the association between laboratory parameters and increased cerebral blood flow velocity in Brazilian SCA pediatric patients. Methods: The study included 159 pediatric patients with SCA, submitted to TCD velocity screening, and the time-averaged maximum mean velocity (TAMMV) was determined in the middle cerebral artery (MCA), anterior cerebral artery (ACA), and distal intracranial internal carotid artery (ICA). We compared cerebral blood flow in patients stratified by the following: TCD1 - defined as normal, with TAMMV inferior to 170 cm/s; TCD2 – conditional, with TAMMV above 170 cm/s, but less than 199 cm/s; TCD3 – altered, with TAMMV greater than or equal to 200 cm/s. Results: TAMMV was negatively correlated with age and weight (p<0.05). Moreover, TAMMV was associated or correlated with reductions in HbF, RBC, hemoglobin, hematocrit, HDL, and haptoglobin and, increases in MCV, MCH, RDW, reticulocytes, WBC, lymphocytes, monocytes, eosinophils, total and indirect bilirubin, LDH, AST, ALT, glucose, ferritin, and AAT (p<0.05). Conclusions: The current study highlights the importance of the investigation of hemolytic and inflammatory biomarkers for monitoring the clinical outcome of SCA pediatric patients, to avoid acute or chronic stroke. Moreover, glucose and HDL-C appear useful for predicting higher TAMMV. Keywords: sickle-cell anemia, stroke, transcranial Doppler, laboratory parameters, TAMMV